THE COMPARATIVE STUDY OF THERMOSTABLE PROTEIN MACROMOLECULAR COMPLEXES (CELL PROTEOMICS) FROM DIFFERENT ORGANISMS (Additives in Polymers, 2015)
D. DZIDZIGIRI, M. RUKHADZE, I. MODEBADZE, N. GIORGOBIANI, L. RUSISHVILI, G. MOSIDZE, E. TAVDISHVILI, and E. BAKURADZEDepartment of Biology Faculty of Exact and Natural Sciences, Iv. Javakhishvili Tbilisi State University, Tbilisi, GeorgiaEmail: d_dzidziguri@yahoo.comINTRODUCTIONIdentification of the functions of proteins and other polymeric complexes or cell proteomes, in which the achievements of proteomics contributes greatly, is the subject of intensive research.1 Modern technology now allows us not only to investigate individual protein molecules in living cell, but also to understand their interaction with other macromolecules and reveal their previously unknown functions. Several facts are determined: participation of polyfunctional macromolecular protein complexes in the biosynthesis of fatty acids, involvement of erythrocyte membrane proteins macromolecular complexes in exchange of CO2/O2, biological effects of some growth factors (polyfunctional proteins), which sometimes is achieved by interactions of other protein complexes, and so on.2-4Earlier, we have identified the protein complex with such properties in various cells of adult white rats.5-7 The main feature of those complexes is the thermostability of the containing components. With gel electrophoreses and chromatography of hydrophobic interaction, it was determined that components with high molecular weight (45-60 kD) are hydrophobic, whereas components with low molecular weight (11-12 kD) are hydrophilic according to the column retention time. Through the inhibition of transcription, complex reduces the mitotic activity of homo-and heterotypic cells in growing animals.5,8 Components of complex are water soluble and is not characterized by species specificity. Thus, we can assume that they are maintained in cells of phylogenetic distance organisms, and in case of confirmation of this fact, they may belong to the conservative family of proteins. In order to determine general regularities of effects of complex described by us, it is necessary to examine in detail the components phylogenesis.